2010
DOI: 10.1080/07347321003648661
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, Religiousness, and Alcoholism Treatment Outcomes: A Comparison between Black and White Participants

Abstract: This study addresses an unexplained finding in the alcoholism treatment field: despite the health and socioeconomic disparities that exist between blacks and whites at intake, blacks and whites achieve equivalent treatment outcomes. Using Project MATCH data, this study explores religiousness and spirituality as strengths in the African American community that may account in part for equivalent outcomes. Using binary logistic regression, this study found that as purpose in life increased, blacks were more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 51 publications
(59 reference statements)
2
37
2
Order By: Relevance
“…This has to be taken into considerationotherwise the (positive) effect of RC styles would be overrated. Moreover, by developing a Multidimensional Inventory of Religious/Spiritual Well-being (see Unterrainer et al, 2010) we were able to confirm that it does make sense to discuss religiosity/spirituality as multidimensional concepts, for example, by differentiating between general religiosity and connectedness or experiences of sense and meaning (see also Krentzman, Farkas, & Townsend, 2010).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This has to be taken into considerationotherwise the (positive) effect of RC styles would be overrated. Moreover, by developing a Multidimensional Inventory of Religious/Spiritual Well-being (see Unterrainer et al, 2010) we were able to confirm that it does make sense to discuss religiosity/spirituality as multidimensional concepts, for example, by differentiating between general religiosity and connectedness or experiences of sense and meaning (see also Krentzman, Farkas, & Townsend, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Hope and forgiveness were found to be low in addiction patients in general, and therefore they might be gainfully addressed as an important topic by the clinician. Furthermore, purpose in life has been reported as a substantial positive therapy outcome predictor (also from a religious/spiritual perspective; Krentzman et al, 2010). Eventually, it may take interdisciplinary working/discussion groups to adequately address all the many facets of spirituality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies depict individuals with different degrees of involvement with alcohol and at different stages. The studies go through a community sample (Drerup et al, 2011), individuals entering a detoxifi cation unit (Norrish & Jooste, 2001), alcohol dependents being treated in outpatient clinics (Krentzman et al, 2010;Robinson et al, 2007), and individuals who are abstinent for at least 10 years from alcohol use (Finfgeld, 1998). Drerup et al (2011) used data from a crosssectional study with an adult community sample (n ϭ 211), in which 65% reported drinking at least some alcohol in the past year, trying to replicate fi ndings from a study of a population of students.…”
Section: General Adult Populationmentioning
confidence: 99%
“…In this study, measures of spiritual aspects are closer to the concept of spirituality. Krentzman et al (2010) used a clinical outpatient sample in a prospective multicentric quantitative study, to access follow-up data on 411 individuals. Information about drinking was collected at baseline and monthly for 15 months.…”
Section: Includedmentioning
confidence: 99%